The Improvement of Knowledge on the Calculation of Cost of Sale and Selling Price for Accommodation Managers in Tegallalang Village - Susanti, Christina; Wiryanata, I.G.N. Agung (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study’s objective is to evaluate the community service initiatives conducted by Prodi Manajemen Akuntansi Hospitaliti at Politeknik Pariwisata Bali, specifically to determine the effectiveness of the socialization and training activities in enhancing participants' comprehension of cost of sale calculation and selling price for accommodation. The activity held at Tegallalang Village on June 7, 2024, and involved 30 participants who are responsible for managing accommodations in the same village. The study approach employed is quantitative, specifically utilizing the One Group Pretest Posttest research model. This involves posing questions both before and after the training. In addition, the data analyzed using a paired t-test with the use of SPSS software. The statistical tests revealed that this activity had a substantial impact on enhancing the participants' comprehension and proficiency in calculating the cost of commodities and determining selling prices for accommodation.